Sodium-Glucose Cotransporter-2 Inhibitors and Cardiovascular Disease: Lessons and the Future - Abdulhalim J. A. Kinsara; Atif Al Qubbany; Wail Alkashkari (Internal Medicine, 2020)
Diabetes mellitus (DM), an epidemic non-communicable disease, is associated with macro- and micro-vascular complications which may result in sudden cardiac death at a young age. Sodium-glucose cotransporter-2 inhibitors (SGLT2-I) emerged as a new therapeutic option for managing DM with cardiovascular complications as well as diabetic patients with multiple risk factors. Three drugs in this class significantly reduced cardiovascular mortality and heart failure events, in both type 2 diabetes mellitus and non-diabetic patients with a reduced ejection fraction, to prevent heart failure related hospitalisation. Evidence of kidney protection was another major advantage provided in more than one study. We reviewed recent SGLT2-I related literature and discuss the benefits beyond the cardiac system.